2019
DOI: 10.1002/14651858.cd009009.pub3
|View full text |Cite
|
Sign up to set email alerts
|

General health checks in adults for reducing morbidity and mortality from disease

Abstract: Trusted evidence. Informed decisions. Better health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
1
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(86 citation statements)
references
References 153 publications
2
79
1
4
Order By: Relevance
“…A recent Cochrane systematic review showed that there is no evidence that general checks in uence morbidity or mortality and this is mirrored in our CDSS. [30] The limited number of tests included in the order set for general check-up shifted the test ordering behavior of GPs in the CDSS arm. We also found that inappropriate laboratory test ordering was very high compared to similar studies.…”
Section: Discussionmentioning
confidence: 99%
“…A recent Cochrane systematic review showed that there is no evidence that general checks in uence morbidity or mortality and this is mirrored in our CDSS. [30] The limited number of tests included in the order set for general check-up shifted the test ordering behavior of GPs in the CDSS arm. We also found that inappropriate laboratory test ordering was very high compared to similar studies.…”
Section: Discussionmentioning
confidence: 99%
“…Screening programmes in the form of primary and secondary prevention general health checks have been investigated28 and found to have limited effects on hard endpoints. The current results show that a high-tech hospital-based programme is strongly preferred by individuals even when the mortality risk reduction was held even between different locations.…”
Section: Discussionmentioning
confidence: 99%
“…In Deutschland werden seit Jahrzehnten, wie in anderen Ländern auch [19], präventive Leistungen im Rahmen von Gesundheitsuntersuchungen (GU) in der Routineversorgung durch Hausarztpraxen erbracht und extrabudgetär honoriert. Diese Leistung gehört gegenwärtig zu den 20 am meisten verwendeten hausärztlichen Gebührenordnungspositionen (GOP) [20].…”
Section: Hintergrundunclassified